Exploring the physical activity and screen-viewing-related knowledge, training, and self-efficacy of early childhood education candidates - Brianne A. Bruijns; Kristi B. Adamo; Shauna M. Burke; Valerie Carson; Jennifer D. Irwin; Patti-Jean Naylor; Brian W. Timmons; Leigh M. Vanderloo; Patricia Tucker (BMC, 2019)
Abstract Background Early childhood educators greatly influence young children's physical activity and screen-viewing behaviours in childcare. However, educators have requested additional training in physical activity programming, and one logical place to provide this education is during their pre-service schooling. This study explored the physical activity and screen-viewing-related knowledge, training, and self-efficacy of early childhood education (ECE) candidates across Canada, to determine their confidence and ability to facilitate physical activity opportunities and limit screen-viewing among young children in childcare. Methods Key program personnel at 61 (of 110) Canadian colleges/universities offering an ECE program agreed to participate in this cross-sectional study. An online survey (112 items; 9 domains), developed by experts using the Tailored Design Method, was administered via Qualtrics© to a sample of 1292 ECE candidates. Descriptive statistics, Mann-Whitney U-tests, and chi-square tests were used to report participant demographics and physical activity and screen-viewing-related knowledge (i.e., of physical activity and screen-viewing concepts), training (i.e., physical activity and screen-viewing courses/content received), and self-efficacy (i.e., to facilitate physical activity and limit screen-viewing in childcare) of candidates. Results ECE candidates exhibited the least amount of knowledge regarding the impact of screen-viewing on physiological outcomes (i.e., blood pressure) in young children. Further, only 32.2 and 26.7% of candidates reported completing physical activity or screen-viewing courses during their post-secondary training, respectively. Candidates who completed one or more physical activity or screen-viewing courses exhibited significantly greater (p <.05) self-efficacy than those without such training related to ensuring children were engaging in adequate moderate-to-vigorous physical activity (MVPA). Confidence to limit screen time did not differ. Candidates reporting meeting national physical activity recommendations (i.e., 150+ minutes of MVPA/week) exhibited significantly greater (p <.05) physical activity-related self-efficacy than those not meeting these guidelines. Conclusions Findings from this work highlight both the need for and the potential of supplementary physical activity and screen-viewing content in post-secondary ECE programs to benefit candidates' knowledge and self-efficacy in these areas. Introducing this content at the post-secondary level will ensure that all early childhood educators are appropriately trained regarding physical activity and screen-viewing before entering a childcare-based profession, where they can positively influence young children's health behaviours.